Analisis Efektivitas Sosialisasi via Media Sosial Seperti Instagram Terkait Kebijakan Perubahan NIK Menjadi NPWP Terhadap Pemahaman Mahasiswa - Ageng Saepudin Kanda S; Eni Siti Nurjanah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This abstract investigates the effectiveness of socialization through social media, especially Instagram, regarding the policy of changing Population Identification Numbers (NIK) to Taxpayer Identification Numbers (NPWP) on student understanding. The use of social media as a tool for disseminating public policy has become the main focus of the government's efforts to convey information to the public. This research examines the level of students' understanding of these changes after being exposed to content on Instagram provided by the government. The research method used was an online survey involving students from various universities. The research results show the extent to which socialization via Instagram is effective in increasing students' understanding regarding changing NIK to NPWP. Data analysis involves evaluating the content, level of participation, and students' understanding of the policy after interaction with the socialization content. The findings highlight the successes and weaknesses of the social media outreach approach. This research provides important insights into the role of social media, especially Instagram, in communicating public policy to younger audiences such as students. The implications of this research can help the government develop more effective strategies in using social media for the dissemination of complex policies, as well as adapting content to increase public understanding.